Mobile app-based education for CAPD self-care in CKD patients: insights from a scoping review - Fransisca Fransisca; Azizah Khoiriyati (Jurnal Konseling dan Pendidikan, 2025)
Chronic Kidney Disease (CKD) requires optimal self-management, especially for patients undergoing Continuous Ambulatory Peritoneal Dialysis (CAPD), where education and adherence play a central role in treatment success. Although the use of mobile health technologies has increased, evidence regarding their educational potential in CAPD care remains fragmented. This scoping review aimed to identify and synthesize existing evidence on mobile app-based educational interventions for CAPD self-management in CKD patients, focusing on the most effective features, learning outcomes, and implementation barriers. A comprehensive literature search was conducted through PubMed, Cochrane Library, ScienceDirect, and Google Scholar for studies published in English from 2014 to 2024, following PRISMA-ScR guidelines. Twenty studies met the inclusion criteria, consisting of eight quantitative, seven qualitative, and five mixed-method designs. The review found that mobile app-based education improved patients’ knowledge, adherence to dialysis procedures, and self-monitoring behavior. The most effective features included interactive educational modules, personalized care reminders, symptom-tracking tools, and two-way communication between patients and healthcare providers. Nevertheless, several challenges were identified, such as limited digital literacy, inconsistent app usability, and lack of integration with clinical systems. These findings indicate that mobile educational applications have strong potential to enhance CAPD self-management by providing accessible, interactive, and patient-centered learning tools, while emphasizing the need for standardized evaluation frameworks and longitudinal studies to assess their long-term effectiveness and clinical impact.